Research and Development of Fire Extinguishing Technology for Power Lithium Batteries. (2018) - Luo, Wei-tao; Zhu, Shun-bing; Gong, Jun-hui; Zhou, Zheng
Abstract: By summarizing the previous experimental studies on fire extinguishing of lithium battery, it was found that the lithium battery fire extinguishing exhibits some essential characteristics, such as long duration, high temperature, large water consumption and great difficulty in extinction. The applicability of fire extinguishing agent for power lithium batteries was analysed in this work. Through the acupuncture experiment, the different efficiencies of fire extinguishing agents were compared. It is expected to provide some useful references for future safety design and prevention of such lithium batteries.